Chromoblastomycosis evolving to sarcomatoid squamous cell carcinoma: A case report - Belda, Walter; Criado, Paulo Ricardo; Casteleti, Paula; Passero, Luiz Felipe Domingues [UNESP] (PAGEPress Publications, 2021)
Chromoblastomycosis (CMB) is a cutaneous fungal infection caused by dematiaceous fungi. According to the World Health Organization CMB has been elected as a tropical disease, and it is prevalent in tropical and subtropical regions. The lower extremities are the most affected areas, and the lesions progress with erythema, papules, nodules, verrucose plates and/or ulcerations. So far, few works have demonstrated neoplastic transformation in chronic CMB lesions, and it may be a consequence of prolonged inflammatory response. In the present case report, we described a neoplastic transformation from CMB lesion of a 55- year-old man, presenting lesions only in the left leg for 35 years. After treatment, a verrucous white plate with thick and irregular borders emerged in the ankle, which was identified as a sarcomatoid squamous cell carcinoma. The present case report highlights the importance of an early diagnosis and treatment.
Keywords: Carcinoma; Chromoblastomycosis; Treatment